The Effect of Radiation Technology on Surface Morphology of Sago Based Eco-friendly Plastic - Rozanna Dewi; Novi Sylvia; Zulnazri Zulnazri (LPPM Universitas Malikussaleh, 2022)
The variety and production continue of plastic has increased and it has brought difficulties in dealing with plastic waste disposed to nature and cannot be decomposed in a long time. Modified thermoplastic starch derived from sago palm crosslinked with polyurethane prepolymer obtained from diphenyl methane diisocyanate and castor oil polyol had better mechanical, thermal and chemical characteristics than bioplastics. In this study, eco-friendly plastics from sago starch modified with prepolymer polyurethane with the addition of chitosan as additive and polypropylene or polyethylene as matrix was produced. The research method conducted were consisting of several stages, preparation of thermoplastic starch, blending thermoplastic starch with polypropylene or polyethylene and plastic irradiation technology using gamma rays with dosage of 5, 10 and 20 kilogray (kGy). The effect of radiation technology on surface morphology of sago based eco-friendly plastic was analysed through Scanning Electron Microscopy (SEM) analysis to observe the effect of gamma rays exposure to the plastic surface. The result showed that the dots appearance on the surface and possibly shown non-uniformity of plastic surface due to less homogeneity of mixture when stirred. Thermoplastic starch was not blended perfectly into PP and this could be due to high temperature different required to melt PP while thermoplastic starch as an organic material cannot stand high temperature and become scorched at high temperature. To overcome this problem, mixing time should be increased to ensure high homogeneity. Overall, SEM analysis showed radiation does not provide effect to plastic surface morphology, which means it did not ruin the polymer structure as well as its binding. Similar appearance observed on the plastic surface morphology before and after radiation, even with highest radiation dose. From the analysis, it can be stated that radiation technology does not influence plastic surface structure, hence plastic binding was remain the same